Public-Service Efficiency Based on Qlue in Jakarta Smart City Development - Ardianto, Yusuf; Nuryakin, Chaikal (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
The purpose of this study is to acknowledge the efficiency level of QLUE application as public-service tool and also as part of Jakarta Smart City development during 2016-2017. The research method was done by applying quantitative approach through descriptive-statistical analysis technique and Data Envelopment Analysis (DEA). The results of the study indicate that Jakarta Smart City development based on information technology, could solve the issues faced by the community and improve public-service. QLUE is one of the application that is being utilized by Jakarta Smart City in receiving reports or people complaints to improve the quality of public-service. Performance efficiency of QLUE in DKI Jakarta showed that the result is still inefficient yet. The whole areas of DKI Jakarta, there were only 74 urban-villages (Kelurahan) shown to be efficient in the performance of public-service based on QLUE during year 2016-2017.